Мы родились в тельняшках: [роман] / Сергей Зверев - Зверев Сергей Иванович (Спецназ, 2016)
Экземпляры: ф.9 (20160808) / Инвентарный номер: 48431 / Цена: 97.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-43 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6